(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The present study was designed to compare rural urban male and female secondary school teachers on teaching competency and personality adjustment. The main objective of the investigation was to know the teaching competency male and female secondary school teachers. To understand the teaching competency of rural/urban male and female secondary school teachers. The sample for the present study consisted of 100 secondary school teachers (50 Govt. Secondary School Teachers and 50 Private Secondary School Teachers) selected randomly from the different schools in various districts of Haryana. In order to assess the teaching competency of private and government secondary school teachers General Teaching Competency Scale by B.K Passi was used. The results revealed that there is significant difference between Private and Govt. Secondary school teachers on their teaching competency.